Formação em cuidados paliativos: apontamentos sobre o processo de ensino na Universidade Federal de São Carlos - Gomes, Maria Caroline Volpin (Universidade Federal de São Carlos, 2022)
The National Academy of Palliative Care argues that the teaching of palliative care must occur systematically in undergraduate and graduate courses, as a way to guarantee qualified assistance to who need. Yet, in Brazil, matrices of essential skills are still being developed. This study sought to understand the teaching scenario on palliative care in health courses at the Federal University of São Carlos. This is a descriptive study, with a mixed approach, developed in two stages: documental study with analysis of pedagogical projects, curriculum matrices and teaching plans; and interviews with teachers who provide contents about palliative care within the scope of the teaching and extension. The information from the documentary data was descriptively organized in Excel spreadsheets and an analysis was based on the fundamentals and principles of palliative care. Thematic analysis was carried out for the contents from the interviews. As a result, it was observed the absence of specific disciplines on palliative care and the scarcity of content on the subject inserted in the disciplines that integrate the curriculum matrix. The difficulties in teaching palliative care from the teachers' point of view are due to the lack of understanding on the subject; the difficulty in providing changes in the curricular structure and the reduced number of qualified teachers in the discipline. It was found that the teaching scenario at this federal university presents significant fragility in training in palliative care, a situation resulting from multifactorial aspects from the perspective of professors. The demand for professional training involving skills that guarantee the recognition of the indication for palliative care in a qualified way is notorious, avoiding late or inadequate referrals in health care, a factor that requires efforts and reflections on strategies that minimize the training gaps identified. In this aspect, it is believed that the development of matrixes of essential competences for the performance of palliative care can favor improvements in the training processes, as well as that initiatives of interdepartmental actions can contribute to the reduction of weaknesses identified in this institution.
Knowledge in palliative care: notes on the teaching process at the Federal University of São Carlos
Keywords: Cuidados paliativos; Ensino; Educação superior; Palliative care; Teaching; Education higher; CIENCIAS DA SAUDE::SAUDE COLETIVA